All about the Party? Constituency Representation—and Service—in Norway. Issue 1 (2nd January 2018) - Heidar, Knut; Karlsen, Rune
Abstract : The article investigates the relationship between Norwegian MPs and their home constituency. The approach is based on the concept of constituency representation, which combines representational focus and constituency service. The data used in the empirical analysis comprise both surveys and in-depth interviews with MPs. It shows that MPs have multiple representative foci. The party is most important, but (party) voters in the constituency are also considered essential. Moreover, MPs actively pursue constituency interests and rate this work very importantly. Indeed, constituency effort represents an essential and time-consuming part of Norwegian parliamentarians' work. They target local policy-friendly organisations and media, and work for general constituency interest simultaneously—when possible also in cooperation with MPs from other parties. In conclusion, the article discusses contextual factors that may contribute to explain MPs' constituency representation in Norway.